Biochemical and Microbiological Assessment of Crucifix Crab (Charybdis feriatus) Stored at 4°C. Issue 4 (21st April 2018) - Anupama, Thottingal K.; Laly, Sundarambal J.; Kumar, Kesavan Nair Ashok; Sankar, Thazhakot V.; Ninan, George
ABSTRACT: Charybdis feriatus is a highly prized crab in the local and international markets of East Asian countries. In local markets, crabs are sold live, iced, or refrigerated at 2°C – 4°C. The present study was carried out to determine the shelf life of whole crab stored at 4°C for 192 h using a set of biochemical, microbiological, and sensorial parameters. Biochemical indicators such as the total volatile base nitrogen (TVB-N) and trimethylamine nitrogen (TMA-N) increased significantly during storage and within an acceptable limit up to 144 h. Regarding the biogenic amines, cadaverine and spermidine increased significantly ( p < 0.05) during the storage period. Among them, cadaverine could be proposed as a useful spoilage indicator for this crab species. The mesophilic and psychotropic bacterial count exceeded the limit of acceptance after 144 h of storage. Sensory attributes were gradually diminished with the storage time. Sensory scores were found to correlate well with both mesophiles and psychrotrophs. Based on the results of this study, the meat quality of Charybdis feriatus can be maintained up to 144 h when properly stored at a temperature of 4°C ± 1°C.